Recent Advances in the Economics of Individual Subjective Well-Being - Alois Stutzer; Bruno S. Frey (University of Basel, Center of Business and Economics (WWZ), 2010)
Over the last decades, empirical research on subjective well-being in the social sciences has provided a major new stimulus to the discourse on individual happiness. Recently this research has also been linked to economics where reported subjective wellbeing is often taken as a proxy measure for individual welfare. In our review, we intend to provide an evaluation of where the economic research on happiness stands and of three directions it might develop. First, it offers new ways for testing the basic assumptions of the economic approach and for going about a new understanding of utility. Second, it provides a new possibility for the complementary testing of theories across fields in economics. Third, we inquire how the insights gained from the study of individual happiness in economics affect public policy.
Keywords: A10; D60; H41; I31; 330; Economics; happiness; life satisfaction; survey data; income; public goods; unemployment; Zufriedenheit; Wirtschaftswissenschaft; Empirische Methode; Wirtschaftspolitik